2012
DOI: 10.5304/jafscd.2012.024.003
|View full text |Cite
|
Sign up to set email alerts
|

Community Supported Agriculture in the City: The Case of Toronto

Abstract: Farming in cities is gaining momentum within North American urban centers. Community supported agriculture (CSA) projects, previously viewed primarily as rural enterprises, are now starting to appear in cities, including Toronto. Urban CSAs address the new food movement's objectives as they can provide good food that is accessible, an income to those growing the food, education on how food is grown, and show the importance of environmental stewardship and the recycling of resources. We used land parcel analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…However, the market value and caloric contribution of CFP per unit area suggests that the potential for CFP to contribute meaningfully to community and household food security is substantial. Findings here are consistent with similar research in Toronto that has suggested the need for scaling up production to meet food insecurity demands (Patel & MacRae, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the market value and caloric contribution of CFP per unit area suggests that the potential for CFP to contribute meaningfully to community and household food security is substantial. Findings here are consistent with similar research in Toronto that has suggested the need for scaling up production to meet food insecurity demands (Patel & MacRae, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Urban and peri-urban agriculture (UPA) has expanded both nationally and internationally over the past two decades (Bellows, Brown, & Smit, 2003;Bruinsma & Hertog, 2003;Patel & MacRae, 2012). The United Nations Food and Agriculture Organization (FAO) reports that 70 percent of the world's urban population participates in urban agriculture in some form (FAO, 2010, p. 1); this produces 15 to 30 percent of the world's food supply (Johnson, 2013).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Farmers also earn a better price by selling the produce directly to the customers. This type of arrangement may produce benefits that extend beyond the use of organic growing practices, since CSA incorporates social justice and community development by helping low-income people and running education activities [17].…”
Section: Resultsmentioning
confidence: 99%
“…markets, on-site sales, and roadside stands. LFSs vary from one community to another based on factors such as crop availability and diversity, delivery options, retail price tolerances, and urban versus rural settings (Patel & MacRae, 2012;Stephenson & Lev, 2004). Productive interaction between and among producers and consumers is a key stimulant to the innovation that is required to sustain and enhance LFSs (Hinrichs, Gillespie, & Feenstra, 2004).…”
Section: Introductionmentioning
confidence: 99%